The impact of remote work on employee-s performance and well-being during the Covid-19 pandemic - the effect of remote work on error management and collaboration - Kütemeyer, Nele Marie (2022)
The Covid-19 pandemic disrupted workplaces -thereby changing work formats and the way of collaborating. The paper “The Impact of Remote Work on Employee’s Performance and Well-Being during the Covid-19 Pandemic” investigates the potential effects of the remote work format on employees’ satisfaction level and its impact on procrastination, taking further into consideration the role of job resources. Results indicate that employees with high remote work satisfaction show low levels of the dysfunctional coping mechanism, namely procrastination. Therefore, remote work satisfaction was identified as a critical concern for employers. The moderator job resources strengthens this relation.